Knowledge, Attitude, and Perceptions about In Vitro Fertilization (IVF) among Women of Childbearing Age in Cape Coast, Ghana. (7th July 2022) - Arhin, Samuel Kofi; Tang, Richard; Hamid, Aisha; Dzandu, Delali; Akpetey, Bright Kwaku
Abstract : Background . Infertility impacts a lot of considerable negative social effects on the lives of infertile partners, especially females, who repeatedly experience the emotional sequelae of childlessness. The study's goal was to assess women of reproductive ages' awareness of IVF treatments, as well as their attitudes and misunderstandings about them in Cape Coast, Ghana. Methods . A total of 437 reproductive-age women in Cape Coast Metropolis were recruited using a simple random sampling approach for this Cross-Sectional Descriptive study. Data were collected with a semistructured interviewer-administered questionnaire and were analyzed using IBM SPSS version 26.0, and p ≤ 0.05 was considered significant. Results . The mean age was calculated to be 25.33 ± 0.066 years with a greater proportion, 65.7% within 15–24 years, 76.5% had no or had never had a child before. 93.4% were of the Christian faith, 66.8% were aware of IVF, and 74.8% think IVF offers hope. Although 41.4% believe it is not a natural procedure and 44.6% believe IVF children are normal but not natural. While 72.1% believe the treatment is very costly, and 40.7% believe it is not affordable or accessible. The majority believe IVF kids are legitimate (76.9%), and so should be welcomed by society (86.5%). The overall opinion of IVF service acceptability was 81.7% good. Seventy-two and three percent did not know whether IVF services are available in Cape Coast. Also, 48.1% were aware that IVF may result in pregnancy failure, with fewer than half (43.5%) believing it could be linked to genetic problems in the baby. The majority (60.4%) were willing to use IVF services, and 82.8% will utilize just their husband's sperm technique. While others may not want to undergo any form of IVF technique because they desire to conceive naturally (51.0%) and 22.4% may be unable to pay for it. Educational status and awareness of the availability of IVF services were factors that were significantly associated with their overall good perception of IVF services. Also, age, marital status, number of live children, occupation, educational status, awareness, and their overall perception were factors that are significantly associated with their preparedness to utilize IVF services. Conclusion . Overall, women's opinions of IVF and their readiness to use them were favorable, and they think it offers hope for their condition since they were well-informed about its forms and that infertility may be a result of several factors, all of which may need IVF services. It does not matter if it is difficult to obtain, expensive, or unavailable. It is recommended that the government collaborates with healthcare providers to investigate ways through the mass media in the drive to clear the misconceptions and improve the public understanding of the IVF procedure towards its utilization, thereby reducing the burden of childlessness and the resulting psychological disorders among couples, this has implications for joyful homes and societal growth.